Analisis tindak tutur ekspresif pada komik doraemon karya fujiko. F. Fujio - Harlita, Prima; , Prof. Markhamah, M.Hum (2016)
Empirically aims to (1) describe a variety of expressive speech acts at work Dpraemon comics Fujiko. F. Fujio, (2) describes the kind of praise the work of Doraemon comic Fujiko.F. Fujio, (3) describe the message of the writer to the reader. Data collection method used is the method see and record. The analytical method used is an orthographic unified method, using basic techniques: sorting technique decisive element atatu PUP techniques. Meanwhile, the presentation of the results of the analysis using an informal presentation. The results of this study are as follows. First, the research found speech acts expressive form of speech acts prohibition, support, angry, begging, complaining, thank you, happy, stating the difficulty, sorry, sorry, apologize, shocked, disappointed, hurt, sad, upset, worried, and afraid. Secondly, it was found praising types: the ability, achievement, or deeds, praised the objects belonging to the speakers, and praised the peaker's personality or friendliness. Thirdly, the message on the comic Doraemon, the message of love and prayer, the message to save money, do not steal, try and pray, give thanks, not arrogant, impatient, we found the message to be: do not take the goods of others by force, do not use any other person recklessly, do not go into people's homes without permission, honest, and the message to be helping.